PENGARUH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN KEBIJAKAN UTANG TERHADAP PENGHINDARAN PAJAK: PENGHINDARAN PAJAK - Sabila Chandra Bestari Komara; Andri (Yayasan Kayyis Mulia Jaya, 2025)
This research aims to analyze the influence of corporate governance, company size, and debt policy on tax avoidance in industrial sector companies in Indonesia during the 2020-2023 period. Corporate governance is measured through managerial ownership structure, institutional ownership, and independent board of commissioners. Company size is measured based on total assets, while debt policy is seen from the debt to equity ratio. Tax avoidance is measured using the effective tax rate (ETR). This research uses quantitative methods with multiple linear regression analysis techniques to test the influence of independent variables on tax avoidance. The data used is secondary data taken from the annual financial reports of industrial companies listed on the Indonesia Stock Exchange during the research period. The research results show that corporate governance, company size, and debt policy have a significant influence on tax avoidance. Corporate governance and debt policy have a positive effect on tax avoidance, while company size has a negative effect. It is hoped that these findings will provide insight for companies, stakeholders and the government in controlling tax avoidance practices in the industrial sector. Keywords: Corporate governance, company size, debt policy, tax avoidance,industrial sector.